Factors affecting acceptance of health information systems in Pakistan - Ujjan, Imran Anwar; Suhaimi, Mohd Adam; Shah, Asadullah (Lahore Garrison University, Lahore, 2024)
For decades, information technology's (IT) acceptance has continued to be a source of contention. Technology Acceptance Models, such as TAM, are utilized to forecast user behaviour. There is little data on the predictive capacity of health information system consumers' approval (HIS). The research focuses on healthcare professionals' Perceived Ease of Use (PEOU) and Perceived Usefulness (PU). All Factors are positive and significant relationships with each other. The first stage is to determine the level of adoption, followed by stakeholders' desire to develop the HIS to improve healthcare services in Pakistan